The Wizard's Touch - Brown, Alice (Saga Egmont, 2023)
‘The Wizard\'s Touch’ (1906) is a short story by American playwright and novelist, Alice Brown. Jerome Wilmer is an artist who returned from his travels to find Mary, the girl he loves, engaged to another. Determined to get her back, he must find a way to win her hand before it\'s too late. This sentimental love story is perfect for fans of romantic fiction and the tangled web of relationships.